PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN DESA WISATA MELALUI KONSEP COMMUNITY BASED TOURISM DAN SUSTAINABLE TOURISM - Muhammad Iqbal (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2022)
Indonesia is a country rich in tourism, so the tourism industry is growing rapidly in Indonesia. Tourism in Indonesia is currently one of the pillars of the Indonesian economy. Indonesia is also currently a tourist destination that is increasingly famous not only among local tourists, but the beauty of Indonesian tourism has been passed on to people in various countries in the world. The progress of tourism goes hand in hand with the rapid development carried out in tourism areas to support tourism infrastructure. However, currently the existence of tourism and its development is still not able to provide great benefits for the surrounding community. In fact, several provinces which are the prima donna of tourism in Indonesia are still provinces with high poverty rates. This study uses a type of library research. The data sources in this study are primary sources and secondary sources. Data collection techniques use documentation, namely reviewing or interpreting written material based on the context. The results of this study indicate that Community-based tourism is a concept of community-based tourism, in CBT the community is empowered to manage their own attractions. One form of CBT is the development of tourist villages.